Human Resource Management in Improving Lecturer Performance at Private Higher Education Institutions - Dudung Hadiwijaya (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Human Resource Management (HRM) plays a strategic role in improving lecturer performance at private higher education institutions, particularly in facing increasing competition, quality assurance demands, and rapid changes in the educational environment. This study aims to analyze HRM strategies and their impact on lecturer performance, including aspects of recruitment, training and development, performance appraisal, compensation, and motivation systems. The research uses a qualitative descriptive approach with data collected through interviews, observations, and document analysis at selected private higher education institutions. The findings indicate that effective HRM practices especially continuous professional development, transparent performance evaluation, and merit-based reward systems significantly contribute to enhancing lecturer productivity, teaching quality, research output, and community service engagement. Institutional leadership support and organizational culture are also found to be critical factors in strengthening HRM implementation. The study concludes that integrated and quality-oriented HRM systems are essential to sustainably improve lecturer performance and institutional competitiveness.